Analisis Pengaruh Motivasi Belajar Siswa, Kinerja Siswa dan Intensitas Pembimbingan Prakerin terhadap Kesiapan Kerja Siswa Keahlian TIK SMKN 1 Nlgegok - Diah Putri Vidia Sari; Satrio Hadi Wijoyo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Work Based Learning (WBL) is the core of vocational training where students build character and a professional work culture in order to prepare students for work or entrepreneurship. TKJ SMKN 1 Nglegok is an educational unit that uses learning materials for the world of work and collaborates with several businesses to provide job prospects to students. This situation can help students enter the world of work according to their fields, but alumni who register to work according to their disciplines still account for 25% to 30% of the total. The problem in this situation, according to the head of TKJ SMKN 1 Nglegok, when exploring problems, learning motivation, student performance, intensity of internship guidance were found to be problems of student work readiness. The purpose of this study was to analyze the effect of learning motivation, student performance and the intensity of internship guidance on work readiness at SMKN 1 Nglegok. This research method is descriptive quantitative. Data analysis used multiple linear regression. according to the T test results , learning motivation had a significant effect on 0.000, student performance had a significant effect on 0.004, and the intensity of internship guidance had a significant effect on 0.010 for work readiness. The F test has a statistical significance of 0.000. The coefficient of determination for the distribution is 66.8 percent. The final result of this study is a recommendation for the implementation of WBL with a description of the real condition of students in aspects of learning motivation, student performance, and intensity of internship guidance for student work readiness.